Functions of Testing In Foreign Language Teaching At A Non-Language University - MATIBAEVA Razia Baltabaevna; RYSBEKOVA Lazzat Kasymbekovna (Peerian Journals Publishing, 2023)
This article examines the functions of testing in teaching a foreign language to students of non-language universities. It considers the implications of testing on the learning process and looks at various test functions from teaching and learning perspectives. The article addresses the importance of this method of assessing a learner’s progress, which provides invaluable feedback on the teaching and learning process. In contrast to subjective forms of assessment, testing provides a more objective measurement of learning outcomes. Thorough analysis of testing results allows for the definition of the learners’ problem areas, the building of foundations for correcting mistakes, and the improvement of the quality of teaching and learning.
Keywords: testing; mistakes; assessment; language